1987
DOI: 10.1524/ract.1987.41.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of PuO2 • xH2Ο in Alkaline Hanford High-Level Waste Solution

Abstract: Plutonium hydrous oxide /Solubility /Hanford high-level waste / NaOH (aq) SummaryThe solubility of Pu(IV) hydrous oxide, PuO, · χ Η, Ο, in airequilibrated synthetic Hanford high-level waste solutions was determined as a function of NaOH, NaAl(OH)", NaN0 3 , NaNO,, and Na, C0 3 concentrations. The solubility was found to increase with the square of the NaOH chemical activity. The components NaN0 3 and NaNO, increased Pu0 2 · χ Η, Ο solubility by increasing NaOH activity. Aluminate increased solubility by the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 8 publications
17
87
1
Order By: Relevance
“…Literature data indicate plutonium exhibits multiple oxidation states in alkaline aqueous solutions. 11,12 Existing studies do not provide definitive identification of Pu oxidation states in the range of solution compositions that will exist during salt solution processing. Identifying the Pu oxidation states and determining the extent and rate of removal of each oxidation state would decrease the uncertainty in predicting Pu removal behavior under varying waste compositions.…”
Section: Fy01 -Future Workmentioning
confidence: 99%
“…Literature data indicate plutonium exhibits multiple oxidation states in alkaline aqueous solutions. 11,12 Existing studies do not provide definitive identification of Pu oxidation states in the range of solution compositions that will exist during salt solution processing. Identifying the Pu oxidation states and determining the extent and rate of removal of each oxidation state would decrease the uncertainty in predicting Pu removal behavior under varying waste compositions.…”
Section: Fy01 -Future Workmentioning
confidence: 99%
“…Solubility data for tetravalent actinides (Rai and Ryan 1983, Rai et al 1995) indicate lack of amphoteric behavior, thus the formation of Pu (OH); species in solution appears to be unproven. However, solubility data obtained by Delegard (1987) The stability constants for Pu(1V) hydrolytic species are listed in Table 2.2. The constants indicate that plutonium in the tetravalent state forms more stable complexes than plutonium in tri-, penta-, and hexavalent states.…”
Section: 2mentioning
confidence: 99%
“…Literature is available that supports the choice of a partially crystalline Pu(IV) oxide described as PuO2~xH2O as the solubility-controlling solid in the 2.11 chemical environments inside a Hanford Site tank. Key references where efforts were made to directly determine the nature of the plutonium solid are Rai et al (1980), Delegard (1987), and Carteret (1996o. Other references that provide empirical data on observed plutonium solution concentrations in chemical environments similar to those inside a Hanford Site tank, but do not attempt to directly determine which solid phase is present, include Hobbs et a1.…”
Section: Precipitation Of Plutonium Hydroxide Phasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Delegard reported that the solubility of Pu in alkaline solutions was strongly influenced by the concentrations of hydroxide, aluminate and nitrate. [5] Given the wide range of the anion concentrations, binary and ternary complexes could be important in some cases. Nitrate and nitrite can serve as oxidizing and reducing agents that would alter the redox characteristics of the solution and, therefore, influence the oxidation state of the Pu.…”
Section: Introductionmentioning
confidence: 99%